Estimation of radioactive 137-cesium transportation by litterfall, stemflow and throughfall in the forests of Fukushima. (November 2015) - Endo, Izuki; Ohte, Nobuhito; Iseda, Kohei; Tanoi, Keitaro; Hirose, Atsushi; Kobayashi, Natsuko I.; Murakami, Masashi; Tokuchi, Naoko; Ohashi, Mizue
Abstract: Since the Fukushima Dai-ichi Nuclear Power Plant accident in March 2011, large areas of the forests around Fukushima have become highly contaminated by radioactive nuclides. To predict the future dynamics of radioactive cesium ( 137 Cs) in the forest catchment, it is important to measure each component of its movement within the forest. Two years after the accident, we estimated the annual transportation of 137 Cs from the forest canopy to the floor by litterfall, throughfall and stemflow. Seasonal variations in 137 Cs transportation and differences between forests types were also determined. The total amount of 137 Cs transported from the canopy to the floor in two deciduous and cedar plantation forests ranged between 3.9 and 11.0 kBq m −2 year −1 . We also observed that 137 Cs transportation with litterfall increased in the defoliation period, simply because of the increased amount of litterfall. 137 Cs transportation with throughfall and stemflow increased in the rainy season, and 137 Cs flux by litterfall was higher in cedar plantation compared with that of mixed deciduous forest, while the opposite result was obtained for stemflow. Graphical abstract: Highlights: Annual flux of 137 Cs by litterfall, throughfall and stemflow was estimated in two types of forest in Fukushima, Japan. Annual amount of 137 Cs transportation was 3.9–11.0 kBq m −2 year −1 in two years after the accident. 137 Cs flux by litterfall was higher in cedar plantation than that of mixed deciduous forest. 137 Cs transportation with throughfall and stemflow increased in rainy season.